Analysis of Incoterms and Payment Terms Preferences for Export Transactions Among Exporters: A Case Study Using an Online Survey - Nur Muhammad Abdillah (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study is entitled "Analysis of Incoterms and Payment Term Preferences for Export Transactions Among Exporters: A Case Study Using an Online Survey". The purpose of this study is to identify the most commonly used Incoterms and Payment Terms by exporters in Indonesia, as well as to analyze the factors that influence their preferences. The research method used is a quantitative approach with an online survey distributed through the Instagram account @overheardekspor, involving 33 respondents who are export companies. From the survey results, it was found that the most widely chosen Incoterms were FOB (Free On Board), which was chosen by 16 respondents, while the most widely chosen Payment Term was Telegraphic Transfer (TT), which was chosen by 26 respondents. The main reasons underlying the choice of Incoterms were lower risk (51.5%) and ease of administration (48.5%). Meanwhile, the main reasons for choosing Payment Terms were transaction security (72.7%) and speed of payment (57.6%). The biggest challenges faced by respondents in choosing Incoterms and Payment Terms are transaction risk (60.6%) and regulatory differences (33.3%). Most respondents suggested choosing Incoterms class C and D and Payment Term TT to gain greater benefits with mature risk considerations. These findings are expected to provide guidance for exporters in choosing the right Incoterms and Payment Terms to reduce risk and increase efficiency in export transactions.